Perlindungan Hukum Rahasia Dagang Menurut No. 30 Tahun 2000 Studi Kasus Putusan Nomor 332 K/Pid.Sus/2013 - ranadi, Gladys felicia; Neltje, Jeane; Berliana, Marsela; Siahaan, Shinta Aulia; Manurung, Rachel Wahyunita Theodor (Jurnal Ilmiah Wahana Pendidikan, 2024)
This writing was carried out using Normative legal research methods using legal case studies, such as legal reviews. This research also uses a prescriptive approach, this approach is carried out by reviewing all regulations related to legal case studies. The Trade Secrets Law was born because it aims to protect the confidentiality of a company so that it is not known by other companies. This is expected to avoid unfair competition. Trade secrets are part of Intellectual Property Rights. This trade secret can be given to information that is considered confidential, where the parties who have mastered the secret have taken steps that have been determined. Law No. 30 of 2000 concerning Trade Secrets is a complement to Law no. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. The concept of trade secrets itself was discovered by the Chinese around 3000 years BC. A form of legal protection between employers and employees is an employment agreement that contains confidentiality clauses.